2012
DOI: 10.1038/ni.2236
|View full text |Cite|
|
Sign up to set email alerts
|

SAMHD1 restricts the replication of human immunodeficiency virus type 1 by depleting the intracellular pool of deoxynucleoside triphosphates

Abstract: SAMHD1 restricts human immunodeficiency virus-1 (HIV-1) infection of dendritic and other myeloid cells at an early stage in the replication cycle. SIVsm/HIV-2 lineage viruses counteract SAMHD1-mediated restriction by encoding Vpx, a virion-packaged accessory protein that targets SAMHD1 for degradation. We show that SAMHD1 restricts HIV-1 infection of monocyte-derived macrophages (MDM) by hydrolyzing the cellular deoxynucleotide triphosphates (dNTP), reducing their level to below that required for the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
858
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 729 publications
(910 citation statements)
references
References 54 publications
34
858
1
6
Order By: Relevance
“…1 clearly demonstrates that the rNMP-mediated pausing disappears when HIV-1 RT synthesizes DNA at a fast rate with elevated dNTP concentrations. In fact, we and others recently reported that the limited dNTP pool found in macrophages is due to the expression of host restriction factor, SAMHD1, which is a dNTP triphosphohydrolase (5,45). Indeed, we also reported that HIV-2 and some SIVs encode an accessory protein, Vpx, that antagonizes the anti-viral function of SAMHD1 by proteasomal degradation.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…1 clearly demonstrates that the rNMP-mediated pausing disappears when HIV-1 RT synthesizes DNA at a fast rate with elevated dNTP concentrations. In fact, we and others recently reported that the limited dNTP pool found in macrophages is due to the expression of host restriction factor, SAMHD1, which is a dNTP triphosphohydrolase (5,45). Indeed, we also reported that HIV-2 and some SIVs encode an accessory protein, Vpx, that antagonizes the anti-viral function of SAMHD1 by proteasomal degradation.…”
Section: Discussionmentioning
confidence: 77%
“…Previously, we have shown that dNTP levels in macrophage are lower than the K m values of RT (4,50). However, Vpx-mediated degradation of SAMHD1 elevates dNTP levels above the K m values of RT (5,50), accelerating proviral DNA synthesis (46). Therefore, we further envision that Vpx-induced dNTP elevation in the non-dividing target cell types enables RTs to effectively overcome the rNMP-induced pausing as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been intensively investigated as a host restriction factor that, in quiescent/differentiated cells, limits HIV-1 and other viral infections by lowering cellular dNTP concentrations under a threshold critical for the synthesis of viral DNA [6]. …”
Section: Introductionmentioning
confidence: 99%